WordPress web application development : build rapid web applications with cutting-edge technologies using WordPress - Ratnayake, Rakhitha Nimesh (Packt Publishing, 2017)
Learn in easy stages how to rapidly build leading-edge web applications from scratch. About This Book Develop powerful web applications rapidly with WordPress Explore the significant features and improvements introduced in WordPress 4.7 by learning the numerous tips and techniques in this book. Unleash the power of REST API endpoints to make your interaction with websites new and innovative. Who This Book Is For This book is targeted at WordPress developers and designers who want to develop quality web applications within a limited time frame and maximize their profits. A prior knowledge of basic web development and design is assumed. What You Will Learn Develop extendable plugins with the use of WordPress features in core modules Develop pluggable modules to extend the core features of WordPress as independent modules Manage permissions for a wide range of content types in web applications based on different user types Follow WordPress coding standards to develop reusable and maintainable code Build and customize themes beyond conventional web layouts Explore the power of core database tables and understand the limitations when designing database tables for large applications Integrate open source modules into WordPress applications to keep up with the latest open source technologies Customize the WordPress admin section and themes to create the look and feel of a typical web application In Detail WordPress is one of the most rapidly expanding markets on the Web. Learning how to build complex and scalable web applications will give you the ability and knowledge to step into the future of WordPress. WordPress 4.7 introduces some exciting new improvements and several bug fixes, which further improve the entire development process.This book is a practical, scenario-based guide to expanding the power of the WordPress core modules to develop modular and maintainable real-world applications from scratch. This book consistently emphasizes adapting WordPress features into web applications. It will walk you through the advanced usages of existing features such as access controlling; database handling; custom post types; pluggable plugins; content restrictions; routing; translation; caching; and many more, while you build the backend of a forum management application. This book begins by explaining how to plan the development of a web application using WordPress' core features. Once the core features are explained, you will learn how to build an applic...